Representation of Science, Technology, and Memory of Postwar Japan in Japanese Anime - Firman Budianto (Bina Nusantara University, 2018)
This research discussed the debates over the development of science and technology in postwar Japan portrayed in Tetsujin 28 anime. Most of the notable anime produced in Japan during 1940s to 1980s were closely related with the memory of wartime, as well as the development of science-and-technology. Tetsujin 28, as one of the anime engaged with the memory of postwar Japan, however, had an interesting storyline representing the debates over development of new technology at the period. By using John Fiske’s semiotics analysis, this qualitative research discussed the way Tetsujin 28 initially created by Mitsuteru Yokoyama (1934-2004) represented postwar Japan, as well as the interface between human and new technology developed during the period. The finding shows that postwar Japan represented in this anime is filled with a great sense of optimism in the middle of modernization. Japan is facing the prosperity era whose development is based on science and technology. Furthermore, the existence of Tetsujin 28 and other robotics technology can be seen as a representation of risk following the development of science and technology. On the other hand, the interface between the robot and human being depicted in this anime, in turn, will pave the way for new forms of life and hope for the prosperous nation.